Hydrological dynamics and its impact on wetland ecological functions in the Sanjiang Plain, China - Xingyu Zeng; Hongqiang Zhang; Boqi Zhou; Xueshi Liang; Ling Cui; Haiyan Li; Yi Qu; Chunyu Luo (Ecological Indicators)
The hydrological environment of wetlands is vital for ensuring the stable development of their ecological functions. However, previous sample-scale studies have failed to capture the spatial heterogeneity of the hydrology-function relationship. The objective of this study is to elucidate the hydrological driving mechanisms responsible for the formation of and changes in the spatial patterns of wetland functions at different spatial and time scales. This study established a multi-dimensional hydrological element and wetland function index system through space technology and multi-source remote sensing images and proposed a multi-scale hydrology-function relationship analysis framework to reveal the relationships between hydrological elements and wetland function spatial patterns at different spatial and temporal scales. The final results demonstrated that, at different spatial and time scales, increasing water coverage contributes greatly to the improvement of habitat, soil conservation, and water supply functions, and increasing the flooding frequency and connectivity structure are more effective at improving the water purification function. At the grid scale, the proportion of grids with medium or strong correlations ranges from 26.63 % to 51.19 %, whereas with respect to temporal correlations, the proportion of grids with medium or strong correlations ranges from 50.67 % to 92.76 %, indicating a pronounced scale effect and spatial heterogeneity of the hydrology-function relationship. The opposite relationships between hydrological elements and functions in some grids (with proportions ranging from 9.89 % to 37.38 %) may result from geographical, environmental constraints, which disrupt the normal correlation between hydrological elements and wetland functions. This study contributes to a deep understanding of the hydrological driving mechanism of wetland functional patterns and provides guidance for wetland protection and restoration planning and hydrological condition regulation by developing specific strategies for improving ecological function.